The origin of chronic inflammatory systemic diseases and their sequelae - Straub, Rainer H. (Academic Press, 2015)
Chronic inflammatory diseases such as rheumatoid arthritis, ankylosing spondylitis, multiple sclerosis, inflammatory bowel diseases, and others typically stimulate a systemic response of the entire body. This response has a uniform character in many diseases because common pathways are switched on. The uniform response regulates systemic energy and water provision. However, long-term application of this program leads to typical disease sequelae such as fatigue / depressive symptoms, sleep disturbances, anorexia, malnutrition, muscle wasting - cachexia, cachectic obesity, insulin resistance, dyslipidemia, alterations of steroid hormone axes, disturbances of the hypothalamic-pituitary-gonadal axis, elevated sympathetic tone, hypertension, volume expansion, decreased parasympathetic tone, inflammation-related anemia, bone loss, hypercoagulability, circadian rhythms of symptoms, and disease exacerbation by stress . The Origin of Chronic Inflammatory Systemic Diseases and Their Sequelae demonstrates concepts of neuroendocrine immunology, energy and water regulation, and evolutionary medicine in order to show that the uniform response that regulates systemic energy and water provision, has been positively selected for acute physiological responses and short-lived disease states, but is a misguided program in chronic inflammatory diseases and aging.